TOTAL QUALITY MANAGEMENT - CHARANTIMATH M POORNIMA (NOIDA PEARSON INDIA EDUCATION SERVICES PVT LTD, 2025)
Poornima M. Charantimath's "Total Quality Management" offers a structured and in-depth exploration of the principles, methodologies, and tools that form the foundation of a total quality-centric organizational culture. The book serves as a comprehensive guide for both students and industry professionals, aiming to instill a thorough understanding of how to achieve excellence in products, services, and processes.
QUALITY MANAGEMENT
BBA & MBA
Keywords: PRADEEP KUMAR BHATTACHARJEE; RISHAB MITTAL; QUALITY MANAGEMENT; MANAGEMENT